Light availability influences the intensity of nectar robbery and its effects on reproduction in a tropical shrub via multiple pathways. Issue 12 (14th November 2020) - Fitch, Gordon; Vandermeer, John H.
Abstract : Premise: The multiple exogenous pathways by which light availability affects plant reproduction (e.g., via influence on attraction of mutualists and antagonists) remain surprisingly understudied. The light environment experienced by a parent can also have transgenerational effects on offspring via these same pathways. Methods: We evaluated (a) the influence of light availability on floral traits in Odontonema cuspidatum, (b) the relative importance of the pathways by which light influences nectar robbery and reproductive output, and (c) the role of parental light environment in mediating these relationships. We conducted a reciprocal translocation experiment using clonally propagated ramets and field surveys of naturally occurring plants. Results: Light availability influenced multiple floral traits, including flower number and nectar volume, which in turn influenced nectar robbery. But nectar robbery was also directly influenced by light availability, due to light effects on nectar robber foraging behavior or neighborhood floral context. Parental light environment mediated the link between light availability and nectar robber attraction, suggesting local adaptation to low‐light environments in floral visitor attraction. However, we found no transgenerational effect on reproduction. Conclusions: Our findings demonstrate that exogenous pathways by which light influences plants (particularly through effects on floral antagonists) can complicate the positive relationship between light availability and plant reproduction. Our results are among the first to document effects of light on floral antagonists and clonal transgenerational effects on flower visitor attraction traits.